Analysis of the Relationship Between Readiness and Interest in Entrepreneurship Among Bunyu Regency Vocational High School (SMK) Students - Sianturi , Donmarth; Baroroh, Kiromim; Sukirno, Sukirno (Journal of Vocational Education Studies, 2024)
Unemployment continues to be a substantial obstacle in several nations, including Indonesia, especially for graduates of vocational high schools (SMK). This research examines the correlation between entrepreneurial preparedness and interest among SMK students in Bunyu Regency, a region characterized by distinctive economic circumstances. This study employed a quantitative method, utilizing descriptive correlational and causal-comparative designs. The study selected 141 students from SMK Negeri 1 Bunyu to represent three distinct academic programs. We meticulously designed questionnaires to collect data, which assessed several dimensions of entrepreneurial preparedness and inclination. The results indicate a strong positive relationship (r = 0.65, p < 0.05) between readiness and interest, with readiness being a significant predictor of interest (β = 0.55, p < 0.05). The findings emphasize the significance of including hands-on entrepreneurship education in the vocational curriculum to improve students' entrepreneurial abilities and decrease unemployment rates among graduates. Furthermore, the research emphasizes the need for focused educational initiatives that specifically target the prevailing economic realities and demands of certain industries. This research offers useful insights to policymakers and educators in developing targeted educational programs, cultivating an entrepreneurial mindset, and promoting sustainable economic growth among vocational school students in distant areas such as Bunyu Regency.